Renewable energy integration practical management of variability, uncertainty, and flexibility in power grids - Jones, Lawrence E. (London Academic Press, 2017)
Renewable Energy Integration: Practical Management of Variability, Uncertainty, and Flexibility in Power Grids, Second Edition, offers a distilled examination of the intricacies of integrating renewables into power grids and electricity markets. It offers informed perspectives from internationally renowned experts on related challenges and solutions based on demonstrated best practices developed by operators around the world. The book's focus on practical implementation of strategies provides real-world context for the theoretical underpinnings and the development of supporting policy frameworks. The second edition considers myriad integration issues, thus ensuring that grid operators with low or high penetration of renewable generation can leverage the best practices achieved by their peers. It includes revised chapters from the first edition as well as new chapters.--Provided by publisher.
Includes bibliographical references and index.
Electronic reproduction.
Keywords: Renewable energy sources; Smart power grids; Electric power distribution; Electronic books